2015
DOI: 10.1186/s13022-015-0013-2
|View full text |Cite
|
Sign up to set email alerts
|

Solitary scalp metastasis – a rare presentation of hepatocellular carcinoma

Abstract: IntroductionHepatocellular carcinoma (HCC) is among the commonest cancers in the world. Metastasis is one of the most significant factors affecting prognosis. Common sites of extrahepatic metastases include lungs, regional lymph nodes and less commonly bone.Case presentationA 56-year-old male presented with a painless occipital scalp lump of three months duration, with recent rapid enlargement. His skull x-ray showed a lytic lesion over occipital bone and the contrast CT scan of the brain showed a scalp mass w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 13 publications
0
30
0
1
Order By: Relevance
“…8 Through an exhaustive bibliographic review, we have noted 25 cases with the skull metastases as the inaugural symptom from HCC and 14 cases with the solitary skull metastases from HCC. [8][9][10][11] In our case skull metastases were the first symptom, but the extension assessment showed other skeletal metastases in sterum, and secondary hepatic nodules. Two pathways of metastatic dissemination can be discussed: the hematogenous pathway that disseminates cancer cells to the liver, lungs, and cerebral parenchyma, then the bone pathway through the venous plexus from Batson to the skull.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…8 Through an exhaustive bibliographic review, we have noted 25 cases with the skull metastases as the inaugural symptom from HCC and 14 cases with the solitary skull metastases from HCC. [8][9][10][11] In our case skull metastases were the first symptom, but the extension assessment showed other skeletal metastases in sterum, and secondary hepatic nodules. Two pathways of metastatic dissemination can be discussed: the hematogenous pathway that disseminates cancer cells to the liver, lungs, and cerebral parenchyma, then the bone pathway through the venous plexus from Batson to the skull.…”
Section: Discussionmentioning
confidence: 95%
“…Clinical suspicion will lead to a biopsy with immunohistochemical study that will confirm the diagnosis, by finding the expression of anti-hepatocyte antibody. 11,12 A complete extension assessment, by brain MRI and thoracoabdominopelvic CT scan, will search for other secondary sites. 12 Therapeutic options remain palliative due to advanced stage of the disease, even in case of isolated cranial metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have reported that the incidence of bone metastasis from HCC increased to 13% and that the most commonly involved sites were the vertebra, pelvis, rib, and skull [ 6 ]. Most HCC patients die of liver failure or internal bleeding without developing clinically apparent extrahepatic metastases [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to gender distribution of primary tumours, we obviously found that the 100% of patients with uterus cancer (8/ 8) 64,65,84 while in 24.8% (30/121) cases, the diagnosis was synchronous. 7,8,18,20,23,31,33,35,44,46,48,56,68,69,72,73,[76][77][78]81,84,87,93,95,96,99,102,110,111 The specific sites of primary tumours in each of these subgroups were reported in Table S1 (Supporting Information). Considering cases diagnosed after the primary tumour, they were mainly derived from breast and GI cancers (18/88 cases each); synchronous cases prevalently had a GI origin (10/30 cases), while cases diagnosed before the primary tumour were only three (one from GI, namely one thyroid and one lung cancer).…”
Section: Demographic and Epidemiologic Datamentioning
confidence: 99%
“…Regarding clinical appearance, AN was identified as a nodule, plaque and patch in 58% (69/119), 8,9,21,22,24,27,33,34,37-41,43,44,46,47,49- 2,6,7,11,[14][15][16][17][18][19][20]23,25,29,67,96 respectively; under the general term of a 'mass' in 16.8% (20/119) 28,32,35,42,45,48,58,59,71,73,80,81,83,87,95,106,110,111,114,117 and as an 'excoriated lesion' in 2.5% (3/119) of cases. 69,78,109 Specifically, breast cancer was mainly associated with patch lesions (9/20), followed by plaques and nodules (five and five out of 20, respectively).…”
Section: Demographic and Epidemiologic Datamentioning
confidence: 99%